Pengembangan Multimedia Pembelajaran Interaktif pada Mata Pelajaran IPS di Sekolah Dasar (SD) Muhammadiyah Program Unggulan Colomadu Karanganyar - Tri Astuti; Nunuk Suryani; Sunardi Sunardi (Teknodika, 2016)
This research aimed to find out:how the needs of learning media for social studies class V in SD Muhammadiyah ProgramUnggulan Colomadu Karanganyar, How is the development of multimedia interactive learning in social studies class V in SD Muhammadiyah ProgramUnggulanColomadu Karanganyar, Effective development of multimedia interactive teaching in subjects IPS class V in SD Muhammadiyah ProgramUnggulanColomadu Karanganyar. The method used method of Research and Development (research and development), but more focused on process development using ADDIE. Stages of development in this study begins with (1) analyzing the needs needed in developing the Product, (2) designing prototypical product, (3) developing the product, (4) implementing the product in the field, and (5) evaluating product’s weaknesses. In addition, this study used totally 56 samples. 28 samples in experimental group (five graders in A class) and 28 samples in control group (five graders in B class). Furthermore, in collecting the data, the researcher used questionnaire and achievement test as the instruments and it was analyzed using Descriptive statistic methods and t-test. The results showed that the media developed has met the worthy and qualified to be used as a learning media. It is seen from the results of expert validation of material with an average of 4.4 and has very good category. Validation of experts media with an average of 4.91 is very good category. According to the students, this multimedia is very good with an average of 4, 60. In the test the learning effectiveness, it is known to the average point obtained by the experimental class is 88.39.  The average point was higher than the control class 73.86.